Left ventricular systolic performance during prolonged strenuous exercise in female triathletes - McGavock, J.; Haykowsky, M.; Warburton, D.; Taylor, D.; Quinney, A.; Welsh, R. (Dynamic Medicine, 2003)
The effect of prolonged strenuous exercise (PSE) on left ventricular (LV) systolic function has not been well studied in younger female triathletes. This study examined LV systolic function prior to, during and immediately following PSE (i.e., 40 km bicycle time trial followed by a 10 km run) in 13 younger (29 ± 6 years) female triathletes.